2017
DOI: 10.21733/ibad.366774
|View full text |Cite
|
Sign up to set email alerts
|

Psi̇koloji̇k Sermaye Ve Di̇ndarlik Eği̇li̇mi̇ İli̇şki̇si̇ne Dai̇r Bi̇r Saha Araştirmasi

Abstract: A Field Research on the Relationship Between Psychological Capital and Religiousness Tendency It is expressed in various theories (ex, Post-traumatic Growth) in which the religiousness tendency increases the status of psychological and spiritual well-being among the influential factors in the development of psychological capital. Increased well-being can also refer more to the religious orientation of the person as the area of spiritual development. In this context, the aim of this research is to show the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Yaşam doyumu kavramı ilk kez 1961 yılında Neugarten tarafından kullanılmıştır (Dede & Türkmen, 2019, s. 2017. Güncel pozitif psikoloji literatürü özelinde de mutlulukla ilgili temel kavramlar incelendiğinde öznel iyi oluş kavramı ile karşılaşılmaktadır.…”
Section: Yaşam Doyumuunclassified
See 1 more Smart Citation
“…Yaşam doyumu kavramı ilk kez 1961 yılında Neugarten tarafından kullanılmıştır (Dede & Türkmen, 2019, s. 2017. Güncel pozitif psikoloji literatürü özelinde de mutlulukla ilgili temel kavramlar incelendiğinde öznel iyi oluş kavramı ile karşılaşılmaktadır.…”
Section: Yaşam Doyumuunclassified
“…However, compared to industrial psychology, positive psychological capital has rarely been studied in other subdisciplines of psychology. In a few studies has analysed the relationship of positive psychological capital with religiousness and spirituality, it was found that there is a positive relationship between these variables (Fatima et al, 2022;Fox et al, 2018;Taş et al, 2017). Even though life satisfaction is one of the most common subjects of positive psychology, there are limited studies on the relationship between life satisfaction and positive psychological capital too.…”
Section: Introductionmentioning
confidence: 99%